Micro RNA‐30b (inhibitor) nanoparticles suppressed the lipopolysaccharide (LPS)‐induced acute kidney injury. Issue 9 (7th November 2019) - Shao, Xiang; Zhang, Suhua; Tang, Ying; Kong, Weixin
Abstract : The main aim of present study is to evaluate the effect of miR‐30b on the function of human proximal tubular epithelial cell line HK‐2 cells. For this purpose, miRNA was loaded in an ionically cross‐linked polysaccharide nanoparticle. The authors have demonstrated the influence of miR‐30b mimic and inhibitor in HK‐2 cell killing effect. Lipopolysaccharide (LPS) significantly increased the level of inflammatory cytokines of TNF‐α, IL‐1β and level was further increased with the treatment of PAg‐miR mimic consistent with the cell viability assay. Interestingly, PAg‐miR inhibitor significantly downregulated the expression of inflammatory cytokines and thereby reduced the inflammation in the body. Western blot analysis showed that LPS induced severe apoptosis of HK‐2 cells and the apoptosis was further promoted by the PAg‐miR (mimic). In contrast, PAg‐miR (inhibitor) alleviated the apoptosis of HK‐2 cells as indicated in the significantly reduced levels of Bax and c‐Caspase‐3 proteins. Overall, miR‐30b promoted LPS‐induced HK‐2 cell inflammatory injury by inducing the apoptosis and by releasing inflammatory cytokines, as well as by impairing autophagy process.